Morphology, lower limbs performance and baropodometric characteristics of elite Brazilian jiu-jitsu athletes - Quintero, A. M.; de la Rosa, A.; Chagnaud, C. A.; Quintero, J. M. G.; Moro, A. R. P. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Brazilian jiu-jitsu (BJJ) athletes are characterized by the mesomorphic somatotype and require great muscular strength and power in the lower limbs in order to perform powerful offensive and defensive actions during combat. Moreover, both pressure and plantar support are very important and have a decisive role in increasing speed and stability during a fight. Problem and Aim. Determine morphological and baropodometric characteristics of elite male BJJ athletes. Methods. Sixteen elite BJJ performed the following test: body composition, unilateral and bilateral counter-movement jump and baropodometric assessment in static conditions. Results. Athletes presented low body fat percentage (10.5 ± 2.2%) and balanced mesomorphic somatotype (2.2- 6.2-1.6). In lower limb strength performance, we observed measures of 41.9 ± 4.7 cm, 1713.4 ± 272 N, and 6.3 ± 4.3 % in vertical jump height, max- imum force and low bilateral asymmetry index percentage respectively. Additionally, baropodometric analysis revealed higher maximum force values in heel and metatarsal zones (p<0.05), in pressure peak and load distribution in the non dominant foot (p<0.05). Moreover, we observed a higher load distribution percentage in the rearfoot surface than the forefoot surface in both the left (61.9% and 37.9%, respectively) and right foot (59.9% and 40.1% respectively). Conclusions. Our results provide useful reference values for morphological and lower limb performance characteristics in elite male BJJ. Moreover, for the first time, baropodometric parameters were evaluated in this population, demonstrating that factors such as plantar pressure and plantar load distribution are greater in the non-dominant foot and in the rearfoot surface of both feet.